Nicotinamide for Keratinocyte Carcinoma Chemoprevention: A Nationwide Survey of Mohs Surgeons. Issue 4 (April 2021) - Desai, Sheena; Olbricht, Suzanne; Ruiz, Emily S.; Hartman, Rebecca I.
Abstract : BACKGROUND: Nicotinamide has been shown to reduce keratinocyte carcinoma (KC) in high-risk patients in a randomized controlled trial setting. Data on nicotinamide's use for KC prevention are limited. OBJECTIVE: To characterize nicotinamide prescribing patterns among Mohs surgeons. METHODS AND MATERIALS: We surveyed 1, 500 members of the American College of Mohs Surgeons regarding their demographics, use of nicotinamide, and safety perceptions. We performed multiple logistic regression analysis to evaluate correlations between physician characteristics and nicotinamide prescribing habits. RESULTS: 76.9% of survey respondents recommend nicotinamide for KC prevention. Twenty percent of respondents have recommended nicotinamide to more than 100 patients in the past year. Forty-five percent of respondents report a duration of use of 2 years or more in their patients. 63.8% of respondents had no concerns over nicotinamide's safety with long-term use. Individuals who answered "yes, " "maybe, " or "uncertain" to having safety concerns over long-term nicotinamide use and individuals in practice for more than 10 years were less likely (odds ratio [OR] 0.30, 95% confidence interval [CI] 0.13–0.71 and OR 0.20, 95% CI 0.05, 0.82, respectively) to have recommended nicotinamide to patients for KC prevention. CONCLUSION: Given the widespread nicotinamide use among Mohs surgeons, additional studies on nicotinamide cost-effectiveness, safety, and use patterns are needed. Abstract : Supplemental Digital Content is Available in the Text.